PENDEKATAN PENGINJILAN TERHADAP PEKERJA SEKS KOMERSIL - Hosana Obidiance Salu Lobo; Yanto Paulus Hermanto; Joko Prihanto (Bethel Press, 2022)
Commercial sex work is one of the jobs that is looked down upon in society at large. This is because the work is an immoral act that harms society. However, the gospel must still be preached to this group, because the gospel is for all mankind. The purpose of this study is to explore evangelistic approaches and methods that are relevant to commercial sex workers in Indonesia. Qualitative methods are used in working on this journal. Several journals, books and Bible verses were collected and compared to answer the problem formulation in this journal, namely the Bible approach to commercial sex. This journal shows the lives of commercial sex workers and how to approach the gospel to their communities, which ultimately results in three effective gospel approach strategies in reaching the commercial sex worker community.